RETRACTED: Isolation and Characterization of Antibacterial Conglutinins from Lupine Seeds - Seham Abdel-Shafi; Mona El-Nemr; Gamal Enan; Ali Osman; Basel Sitohy; Mahmoud Sitohy (Molecules, 2022)
The main target of this work is to discover new protein fractions from natural resources with high antibacterial action. The 7S and 11S globulin fractions, as well as the basic subunit (BS), were isolated from lupine seeds (Lupinus termis), chemically characterized, and screened for antibacterial activity against seven pathogenic bacteria. SDS-PAGE revealed molecular weights ranging from 55 to 75 kDa for 7S globulin, 20–37 kD for 11S globulin, and 20 kD for the BS. 11S globulin and the BS migrated faster on Urea-PAGE toward the cathode compared to 7S globulin. FTIR and NMR showed different spectral patterns between the 7S and 11S globulins but similar ones between 11S globulin and the BS. The MICs of the BS were in the range of 0.05–2 ?g/mL against Listeria monocytogenes, Klebsiella oxytoca, Proteus mirabilis, Staphylococcus aureus, Listeria ivanovii, Salmonella typhimurium, and Pseudomonas aeruginosa compared to higher values for 11S globulin. The BS surpassed 11S globulin in antibacterial action, while 7S globulin showed no effect. The MICs of 11S globulin and the BS represented only 5% and 2.5% of the specific antibiotic against L. monocytogenes, respectively. Scanning electron microscopy (SEM) demonstrated different signs of cellular deformation and decay in the protein-treated bacteria, probably due to interaction with the bacterial cell wall and membranes. 11S globulin and the BS can be nominated as effective food biopreservatives.